KESETARAAN: SOLUSI PERBAIKAN BANGSA (INTERPRETASI KRITIS KIDUNG AGUNG 7:10 – 8:4 DALAM PERSPEKTIF GENDER) - Roy Charly H. P. Sipahutar (Institut Agama Kristen Negeri Tarutung, 2019)
AbstractThis paper is an attempt to reinterpret the Song of Songs 7:10 - 8: 4 using the Critical Historical approach in a gender perspective. The Critical Historical Approach is a method of interpretation that emphasizes historical findings, both the history of the text and the history of the context of the text. For a very long time this passage has been interpreted allegorically, human relations with God are like lovers, but this time the text will be interpreted more freely and let it speak independently of traditional concepts of thought. The Song of Songs 7:10 - 8: 4 was written in the Babylonian Exile when the Persian Empire ruled the land. In socio-historical terms, the text can be understood to offer a new concept for the improvement of the nation which at that time needed new strength, namely gender equality between men and women. Equality of both sexes is an idea that is a great leap in that era.Key Words: Song of Songs 7:10 -8: 4, Interpretation, Gender Perspective, Equality.